Knowledge Translation from Research to Clinical Practice: Measuring Participation of Children with Disabilities. Issue 4 (1st October 2016) - Jeong, Yunwha; Law, Mary; DeMatteo, Carol; Stratford, Paul; Kim, Hwan
ABSTRACT: This knowledge translation project was conducted to increase occupational therapy practitioners' awareness of the importance of measuring participation of children with disabilities. The Knowledge to Action process framework (KTA framework) guided knowledge translation via a web-based seminar (webinar) to practitioners working with children and educators teaching in occupational therapy programs in South Korea. Two hundred and seventy six views of the webinar were recorded within a month and 15 practitioners and 13 educators completed the online evaluation survey. The participants indicated that the webinar helped them understand the participation concept and its associated measures and raised awareness of practitioners' current use of measurement and intervention that do not focus on participation of children with disabilities. This project led practitioners and educators to realize the importance of measuring participation of children with disabilities and contributes to inform the importance of knowledge translation science to facilitate the evidence-based practice.